The Influence Of Social Media Content And Brand Awareness On The Purchase Decisions Of Generation Z For Sender Coffee - Aziz, Maulana Abdul; Widyatama, Rendra (Universitas Muhammadiyah Pontianak, 2025)
This study examines the influence of social media content and brand awareness on purchasing decisions of Sender Coffee products among Generation Z at Ahmad Dahlan University, Yogyakarta. Generation Z is highly engaged on social media and often uses digital content to make purchasing decisions. This research contributes originality by focusing on a local coffee brand that employs a narrative approach in its digital marketing strategy. The study adopts a quantitative, causal design. Data were collected via an online questionnaire distributed to 67 respondents selected through purposive sampling. After passing validity, reliability, and classical assumption tests, the data were analyzed using multiple linear regression. The results show that social media content and brand awareness significantly affect purchasing decisions, partially or simultaneously, with a combined influence of 42.9%. These findings underscore the importance of integrating visually engaging content with consistent brand awareness efforts. The practical implication is that local businesses such as Sender Coffee must build emotionally resonant and consistent digital communication strategies tailored to young consumers' preferences.